Synthesis of Platinum Nanoparticles Conjugates of Ceftriaxone and its Schiff Bases Using Sodium Borohydride and Trisodium Citrate - Abdulghani, Ahlam Jameel; Mohuee, Saja Khalil (Asian Journal of Chemistry, 2016)
The synthesis of platinum nanoparticles conjugates was achieved by the reduction of hexachloroplatinic acid with sodium borohydride (NaBH4) and trisodium citrate in aqueous solutions using ceftriaxone and two Schiff base ligands derived from ceftriaxone sodium with 1H-indole-2,3-dione (isatin), L1 and 1-acetyl indoline-2,3-dione (N-acetylisatin) L2 as capping agents. The synthesized platinum nanoparticles were characterized by UV-visible spectrophotometry, X-ray diffraction, scanning electron microscope and atomic force microscope analysis. Conjugation of the ligands with the nanoparticles was characterized by FT-IR spectrophotometry.